Análise da aplicação do protocolo de eletrolipólise recomendado pelo fabricante para redução do panículo adiposo abdominal - Mattana, Luciana (2022)
The accumulation of body fat in the abdomen is directly associated with metabolic syndrome, dyslipidemia and cardiovascular diseases. In addition, there is a loss of body contour in women, a condition that directly affects the self-esteem of this population. Several technologies have been developed to treat the problem, however, there is a lack of scientific evidence regarding the effectiveness of the protocols. The aim of this study was to test the manufacturer’s suggested electrotherapy protocol (ELP) for subcutaneous fat reduction and waist circumference measurements in women aged 35 to 45 years. The aforementioned protocol establishes a fixed frequency parameter at 5Hz without dosage and applicability time. To evaluate the same as the reduction of subcutaneous fat and volume of the abdominal region, anthropometric measurements (perimetry and mass), adipometry and ultrasound were used. Thirty women aged between 35 and 45 participated in the study, all of whom received six ELP sessions using a dosage of 4 mA and the frequency of 5Hz suggested by the equipment manufacturer. Comparative data were collected in the 1st; 3rd and 6th session. The volunteers were sedentary and were not undergoing a dietary control process, with a mean age of 41.6 years ± 3.3 years, mean weight of 69.6 kg ± 10.6, mean height of 1.62 m ± 0.1. The abdominal circumference of the volunteers was around 90.7 cm ± 9.9 and skinfold of 37.1 mm ± 19.2. As a result, no significant anthropometric differences were detected at any time during the protocol application. The analysis performed by ultrasound also found the absence of a significant result in the reduction of abdominal fat in the participants. Comparing the 1-3rd day, 3-6th day and 1-6th day, p values equal to 0.936, 0.314 and 0.613 were obtained, respectively. After analyzing the data, it can be concluded that the studied group did not present changes in relation to their body composition after the application of the technique.